RoCHI - International Conference on Human-Computer Interaction 2020
DOI: 10.37789/rochi.2020.1.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Usability Testing of Mobile Augmented Applications for Cultural Heritage – A Systematic Literature Review

Abstract: This paper presents an overview of the existing literature to date regarding the usability testing of Mobile Augmented Reality applications developed for cultural heritage. A Systematic Literature Review was conducted with this purpose. Four databases were interrogated with specific keywords. Our of the 88 found research papers, only 31 met the eligibility criteria to be included in this survey. Four major usability testing methods were identified: questionnaires, focus groups, user testing and interviews. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Este es el caso, por ejemplo, del trabajo pionero del proyecto ARCHEOGUIDE (Vlahakis et al, 2001) donde, tras su aplicación en el yacimiento griego de Olimpia, se sintetiza el resultado de un cuestionario en el que se verifica la buena recepción de los usuarios a este sistema, especialmente en el público joven. En otras contribuciones sobre Realidad Aumentada se desarrollan planteamientos y resultados similares (Cinotti et al, 2004;Galatis et al, 2016;Tiriteu & Vert 2020;Cisternino et al, 2021). Cabe destacar el análisis de la aplicación móvil de Realidad Aumentada multisensorial empleada en el yacimiento romano de Conimbriga (Portugal), que evidencia el valor añadido que ofrece la tecnología de Realidad Aumentada para la difusión del patrimonio arqueológico con una amplia aceptación por parte del de las personas usuarias (Marto et al, 2016;Marto & Gonçalves, 2019).…”
Section: Web Of Scienceunclassified
“…Este es el caso, por ejemplo, del trabajo pionero del proyecto ARCHEOGUIDE (Vlahakis et al, 2001) donde, tras su aplicación en el yacimiento griego de Olimpia, se sintetiza el resultado de un cuestionario en el que se verifica la buena recepción de los usuarios a este sistema, especialmente en el público joven. En otras contribuciones sobre Realidad Aumentada se desarrollan planteamientos y resultados similares (Cinotti et al, 2004;Galatis et al, 2016;Tiriteu & Vert 2020;Cisternino et al, 2021). Cabe destacar el análisis de la aplicación móvil de Realidad Aumentada multisensorial empleada en el yacimiento romano de Conimbriga (Portugal), que evidencia el valor añadido que ofrece la tecnología de Realidad Aumentada para la difusión del patrimonio arqueológico con una amplia aceptación por parte del de las personas usuarias (Marto et al, 2016;Marto & Gonçalves, 2019).…”
Section: Web Of Scienceunclassified
“…These complex digital products have been evaluated in a multi-platform setting, i.e., touchscreen table, desktop/laptop, mobile, and Augmented Reality. The user evaluation followed a mixed methods approach, to respond to the stringent need for multiple platform evaluation and comprehensive user testing [1]. Spotlight Heritage is a multi-annual project and from our previous evaluation and use cases, we identified that users navigate seamlessly between different platforms-they might initiate it online, on the website, then move and continue the exploration on the mobile app, go and visit the physical exhibition and use the interactive display, or visit one of the landmarks in location and use the augmented reality app.…”
Section: Spotlight Heritage Evaluation Studymentioning
confidence: 99%